1996
DOI: 10.1007/bf02823878
|View full text |Cite
|
Sign up to set email alerts
|

Iodine deficiency disorders in Bangladesh

Abstract: An extensive iodine deficiency disorders survey was conducted in Bangladesh in 1993 to assess the latest iodine nutriture status of the country. The clinical variables of the survey were goitre and cretinism, and the biochemical variable was urinary iodine. The "EPI-30 cluster" sampling methodology was followed for selecting the survey sites. In each survey site, the study population consisted of boys and girls, aged 5-11 years, and men and women, aged 15-44 years, in about equal populations. The total number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…In 1993, the prevalence of goitre in Bangladesh was 47.1%, cretinism 0.5%, and sub-clinical iodine deficiency (low urinary concentration of iodine <100 µg/L) 69% (32). The latest Iodine Deficiency Disorder (IDD) Survey showed that the prevalence of goitre among 6-12 years old children was 6.2%, and it was 11.7% among women aged 15-44 years (33).…”
Section: Resultsmentioning
confidence: 99%
“…In 1993, the prevalence of goitre in Bangladesh was 47.1%, cretinism 0.5%, and sub-clinical iodine deficiency (low urinary concentration of iodine <100 µg/L) 69% (32). The latest Iodine Deficiency Disorder (IDD) Survey showed that the prevalence of goitre among 6-12 years old children was 6.2%, and it was 11.7% among women aged 15-44 years (33).…”
Section: Resultsmentioning
confidence: 99%
“…In our study the prevalence of goitre was 28.13%, of which grade 1 goitre was 21.96% and grade 2 goitre was 6.17%. Three major surveys -the than East Pakistan Nutrition Survey of 1962-64, the National Goitre Prevalence Study of 1981-82 and the National Iodine Deficiency Disorders Survey in Bangladesh-1993 showed prevalence rates of goitre in this country to the extent of 20%, 10.5% and 47.1% respectively 5 . Alam F…”
Section: Discussionmentioning
confidence: 98%
“…A survey conducted in Bangladesh in the year 1993, showed that prevalence of goiter was 47.1% and cretinism was 0.5%. They observed that 69% of Bangladeshi had biochemical iodine deficiency 14 .…”
Section: The Status Of Thyroid Hormones In Iron Deficient Patients Inmentioning
confidence: 99%